FREE RADICAL PROCESSES ACTIVITY IN BLOOD SERUM OF WOMEN WITH HIGH-RISK PREGNANCIES AND ON THE IMPACT OF INFORMATION PRODUCTS - A. A. Nikashina; I. I. Krukier; A. E. Kudaev; N. K. Khodareva; S. V. Kruglova (Медицинский вестник Юга России, 2013)
Purpose: To study the activity of free radical processes and anti-radical defense enzymes in the serum of women with miscarriage, as well as the effect of information drug serum of women said the contingent (in the experiment).Materials and methods: Blood serum of 48 women in the first trimester of pregnancy was studied. To assess the state of free radical oxidation the following indicators used: the level of nitric oxide (NOx), peroxynitrite, NO-glutathione, NO-tyrosine and the activity of catalase.Results: The coefficient of peroxynitrite / NO-tyrosine was calculated. Also the data on the impact of information products (IP) on free radical processes in blood serum of women with high-risk pregnancies is contains.Summary: The coefficient (peroxynitrite / NO-tyrosine) can be used as a diagnostic criterion of threatened abortion and evaluating the effectiveness of treatment of pregnancy complications.